Pemasaran Wisata Edukasi Berbasis Potensi Sumber Daya Alam Melalui Media Sosial (Studi Kasus: Desa Sumber, Kecamatan Dukun, Kabupaten Magelang) - Nurmiyati Nurmiyati; Niken Utami Tyastuti; Annida Sifa Utami; Novi Arifatul Azizah (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2021)
Sumber Village which is located in Dukun District, Magelang Regency is one of the villages that has the potential for educational tourism that can be developed. The existence of people who make a living as cobek stone craftsmen, pothil food producers, farmers, and breeders can be used as a place to learn new things. However, this educational tour still needs to be promoted online so that it is known to many people. Therefore, the service activities carried out are marketing of educational tourism based on the potential of natural resources through social media. The purpose of these activities is to promote educational tourism and the potential of the village to the general public. The method used is coordination with the Sumber Village apparatus, conducting surveys, interviews, taking photos, creating social media accounts, uploading content, providing direction and assistance to tourism managers. The results of this activity are the existence of social media accounts for educational tourism in Sumber Village and Cobek SMEs, as well as the understanding of tourism managers in using social media for promotion.